2014 ACM/IEEE International Conference on Cyber-Physical Systems (ICCPS) 2014
DOI: 10.1109/iccps.2014.6843716
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificing a little space can significantly improve monitoring of time-sensitive cyber-physical systems

Abstract: The goal of runtime verification is to inspect the correctness of a system by incorporating a monitor during its execution. Predictability of time distribution of monitor invocations and memory usage are two indicators of the quality of a monitoring solution, specially in cyber-physical systems, where the physical environment is a part of the system dynamics. In our previous work, we proposed a control-theoretic approach for coordinating time predictability and memory utilization in runtime verification of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Each technology breakout had led to the rapid development of manufacturing industry. Today, the German government officially puts forward industry 4.0 strategy, which integrated industrial robots, networking, cloud manufacturing, and other advanced technology to build a highly intelligent industry 4.0 system [1][2][3]. Some researchers who came from research institutions and universities as well as SIEMENS, BMW, and other companies have built up research teams, trying to make an intelligent and automated industry 4.0 system [4].…”
Section: Introductionmentioning
confidence: 99%
“…Each technology breakout had led to the rapid development of manufacturing industry. Today, the German government officially puts forward industry 4.0 strategy, which integrated industrial robots, networking, cloud manufacturing, and other advanced technology to build a highly intelligent industry 4.0 system [1][2][3]. Some researchers who came from research institutions and universities as well as SIEMENS, BMW, and other companies have built up research teams, trying to make an intelligent and automated industry 4.0 system [4].…”
Section: Introductionmentioning
confidence: 99%
“…The time-triggered monitoring needs to find an optimal sampling period, so that the required auxiliary memory will be minimized and the monitor still correctly tracks the program state. In [Medhat et al, 2014], a control-theoretic approach was proposed to improve the time predictability, and ensures the soundness of verification by incorporating a maximally utilized bounded memory buffer. Experimental results of monitoring the functioning of a Toyota 2JZ engine showed that the overshoots were reduced and the time predictability was improved by applying this control-theoretic monitoring approach.…”
Section: Related Workmentioning
confidence: 99%